Biological activity of entomopathogenic nematodes on Anastrepha fraterculus (Diptera: Tephritidae) (Bioscience Journal, 2021)
Anastrepha fraterculus (Wiedemann) is one of the main pests of fruit farming, and entomopathogenic nematodes (EPNs) represent an important control tool of this species. Thus, the objective of this study was to evaluate the biological activity of different isolate against A. fraterculus larvae and adults. Bioassays were performed using a suspension of three isolates of Heterorhabditis amazonensis IBCB 24, Steinernema carpocapsae IBCB 02 and Steinernema feltiae IBCB 47 at six concentrations (control - without nematodes), 50, 150, 300, 500, 1000 and 1500 infective juveniles (IJs)/mL of water per 3º instar larvae. It was verified the susceptibility of larvae of A. fraterculus to isolates of EPNs and a significant increase of the pupal mortality in the function of the concentration of IJs inoculated by larva (above 75%). After the dissection of pupae and adults of A. fraterculus from infected larvae, the concentration of 1500 IJs/mL of EPNs provided the highest rate of multiplication of IJs by insect, equating to maximum concentration tested 1500 IJs/mL. Adults of A. fraterculus from larvae infected with EPNs longevity of five days, being less than adults from uninfected larvae by IJs (135 days). H. amazonensis IBCB 24, S. carpocapsae IBCB 02, and S. feltiae IBCB 47 proved to be promising as agents of biological control of A. fraterculus.